Modern Slavery Policies in a Conceptual Perspective - Sarihasan, Imran; Máté, Domicián (International Journal of Engineering and Management Sciences, 2018)
Most of the people assume modern slavery end up in 19th century. However, according to the International Labor Organization (ILO), today 40 million people live as a slave. Moreover, modern slavery is the world’s fastest growing crime and has huge number, which never occurred in history before. One of the main limitation of the existing literature on contemporary slavery is that it ignores the history of slavery either entirely or alternatively between past and present. However, this article aims to figure out the role of modern slavery, also recommends some suggestions to governments to solve the problem of it. The aim of this paper is to addressing to the modern slavery policies in a conceptual perspective. In the theoretical framework of modern slavery, rational choice theory, conflict theory and human security theory have been selected to describe the sequence of modern slavery.